Atrocious dietary habits leading females of Karachi towards Polycystic Ovary Syndrome - Noushad , Shamoon; Afzal, Sidra; Barkat, Neelam; Ahmed , Sadaf; Shah, Nighat (International Journal of Endorsing Health Science Research, 2015)
Introduction Polycystic ovary syndrome (PCOS) is the most common chronic endocrine disorder that is responsible for imbalance of hormones affecting women of reproductive age leading to difficulties in period cycle and getting pregnant. Objective The aim of study was to evaluate the routine eating habit of the patients. Methodology The study was conducted in Gynecology ward of Tertiary care hospital. This analytical study was performed after taking consent including those patients, who came to the clinic to report their problem of infertility (married women) and irregular periods problems (unmarried girls), targeted age group was between 25 to 35. Interview based study was conducted which include all the questions related to their eating habits like; food typically eaten in breakfast, lunch, dinner and amount of snacks taken per meal. High intake of carbohydrate and fats also investigated per meal. There BMI and FBS was also calculated. Results Total 300 patients were studied out of which 50 patients were included in the study and the results showed that in PCOS patients the frequency of obesity & overweight is (92%), followed by (66%) of patients had excess carbohydrate/sugar craving while 34% patients had normal eating patterns. High rates of these complications were seen in the series. Conclusion From the results it is suggested that obese women with PCOS requires more attention toward the appropriate management of their dietary habits , as their high BMI and high fasting blood sugar is correlating with abnormal clinical and biochemical features. Calorie intake should be restricted. Diet control along with exercise was suggested to the patients.